2020
DOI: 10.1186/s13102-020-00165-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise on fatigue in hemodialysis patients: a randomized controlled trial

Abstract: Background: Hemodialysis is one of the common therapies in patients with end-stage renal disease. Even patients who receive regular treatment suffer from fatigue, which is one of the main factors leading to poor quality of life. This study aimed to determine the effectiveness of exercising on mini-bikes on fatigue in hemodialysis patients. Methods: This study is a randomized controlled clinical trial. Thirty-seven hemodialysis patients participated in the study. The patients were randomly allocated to either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
0
31
0
4
Order By: Relevance
“…In Case 3, fatigue related to CKD may have affected presenteeism. A previous study showed that exercise therapy in patients with CKD reduces fatigue [ 24 ]. Additionally, physical function is related to fatigue in workers [ 25 ], and exercise therapy for workers has been shown to reduce fatigue [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Case 3, fatigue related to CKD may have affected presenteeism. A previous study showed that exercise therapy in patients with CKD reduces fatigue [ 24 ]. Additionally, physical function is related to fatigue in workers [ 25 ], and exercise therapy for workers has been shown to reduce fatigue [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, hemodialysis patients are less engaged in physical activities on dialysis days and preliminary results demonstrate that low-to-moderate-intensity exercise prior to hemodialysis is effective in improving fatigue [ 42 ]. One small-scale randomized clinical trial also demonstrated intradialytic exercise was efficacious in reducing fatigue in the intervention group compared to the control group [ 43 ]. From clinical perspectives, our results reinforce the importance of maintaining the recommend minimum target of nPCR of 1.2 g/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Today, physical activity is one of the simplest and possibly the most inexpensive strategies for improving the lifestyle of cardiovascular patients [ 8 ]. Physical activity is any physical movement that requires energy expenditure and is generated by skeletal muscle [ 9 ]. Physical activity can moderate risk factors in heart failure patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%